The influence of ability to identify criteria on feedback acceptance - Martin, Angela, author; Gibbons, Alyssa Mitchell, advisor; Henle, Chris A., committee member; Rhodes, Matthew G., committee member; Thornton, George C., committee member (Colorado State University. Libraries, 2013)
The criteria used in selection methods such as interviews, integrity tests and assessment centers are often unknown to candidates seeking employment. The individual difference variable of ability to identify criteria (ATIC) represents the degree to which some candidates are better able to correctly identify the situational demands in an ambiguous situation (Kleinman, 1993). Prior research has shown that ATIC is related to performance in the selection method and cognitive ability (Melchers et al., 2009). I tested whether two measures of candidates' ability to identify criteria (ATIC) in an assessment center exercise were related to cognitive ability, social intelligence, self-monitoring and feedback acceptance. Contrary to prediction, we found minimal relationships among measures, raising interesting questions regarding the nomological net and construct validity of ATIC measures.
Keywords: ability to identify criteria; feedback